Corneal Deposit of Ciprofloxacin after Laser Assisted Subepithelial Keratomileusis Procedure: A Case Report - Giacomo De Benedetti; Andrea Brancaccio (Journal of Ophthalmology)
Purpose. To report one case of corneal antibiotic deposition after ciprofloxacin administration in Laser Assisted Subepithelial Keratomileusis (LASEK). Methods. One case of post-LASEK treatment resulted in corneal precipitates and poor wound healing. Debris was analyzed with dark field microscopy and placed on a blood-agar plate seeded with a susceptible stain of Staphylococcus aureus (ATCC 29213). Results. The alterations resolved with discontinuation of ciprofloxacin treatment, although some residual deposits persisted subepithelially for 6 months. Analysis of precipitates revealed polydisperse crystalline needles of 183 𝜇m average length (SD=54 𝜇m) and the excised precipitate demonstrated a zone of inhibition. Conclusions. Fluoroquinolone antibiotic drops have been used extensively in postsurgical treatment of refractive surgery. Corneal precipitates have been previously reported in the literature, but up to now nothing has been documented after LASEK. Polypharmacy during refractive surgery may impair epithelialisation, and clinical management should reduce toxic environment and promote ocular surface stability when performing surface ablations.